PENGEMBANGAN MEDIA AUDIO VISUAL BERBASIS KONSTRUKTIVISME MELALUI APLIKASI CANVA PADA MATERI BILANGAN BULAT DI KELAS VII MTs PP DARUL FALAH - Putri Salma; Adevi Murni Adel; Hana Adhia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This development research (R&D) aims to design constructivism-based audiovisual learning media through the Canva application for integers topic targeted at seventh-grade students of MTs PP Darul Falah. The primary focus of this study is to measure the validity and practicality of the developed instructional tool. Following the ADDIE framework, the research comprises five systematic phases: Analysis, Design, Development, Implementation, and Evaluation. The subjects involved in this study were 27 seventh-grade students. The empirical findings demonstrated that the media is highly valid, indicated by expert validation scores: 82.5% from media experts, 95.5% from material experts, and 94% from language experts. Additionally, the student questionnaire responses revealed a practicality score of 90.33%, positioning the media in the highly practical category. In conclusion, the constructivism-based audiovisual media created via Canva is psychometrically valid and practical for mathematics instruction.